Christ Church on Salem Street, ca. 1860-90 - Unknown (Tufts Archival Research Center, 2005)
Street-level view southeast of Christ Church, located on Salem Street at the southeast end of Hull Street. The facade of the church faces northwest. Street lights adorn some of the facades of the buildings lining both the northeast and southwest sides of Hull Street. Two people are visible on Salem Street. Designed by William Price, 1723; also known as the Old North Church 7 3/8 x 3 7/8, 8 1/4 x 6 3/19 overall Photographs